THE IMPLEMENTATION OF LAW NUMBER 16 OF 2019 POLICY CONCERNING THE MINIMUM AGE FOR MARRIAGE IN BANUA LAWAS SUB-DISTRICT, TABALONG REGENCY - M. Noor Fuadi; M. Husaini; Wardatun Nisa (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
Marriage age maturation is a strategic effort to increase the age of first marriage in order to achieve an ideal age for building a family. The implementation of Law Number 16 of 2019 concerning the minimum age of marriage in Banua Lawas District, Tabalong Regency, has not yet achieved optimal results. This situation is indicated by the persistently high rate of early marriage, despite the legal stipulation of a minimum marriage age of 19 years for both males and females. This condition is influenced by limited public awareness and understanding, as well as weak coordination among related institutions. This study aims to analyze the implementation of Law Number 16 of 2019 regarding the minimum marriage age and to identify factors influencing its implementation in Banua Lawas District, Tabalong Regency. A qualitative descriptive approach was employed in this research. Data were collected through interviews, observations, and documentation, with informants selected using purposive sampling involving 12 participants. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of Law Number 16 of 2019 concerning the Minimum Age of Marriage in Banua Lawas Subdistrict, Tabalong Regency, is still not optimal. This can be seen from several indicators that are considered inadequate, including policy clarity, policy objectives, human resources, financial resources, acceptance, rejection, relations between employees and the community, relations between employees and other institutions, and social conditions. The indicators categorized as good include firmness, strictness, rigidity, and economic conditions, while political conditions are considered fairly good. Supporting factors include disciplined policy implementers and stable economic conditions, whereas inhibiting factors consist of limited socialization, budget constraints, and a lack of public awareness. To improve the implementation of Law Number 16 of 2019 in Banua Lawas District, it is recommended that the Office of Religious Affairs strengthen community outreach programs, enhance coordination with village governments and community leaders, and encourage active community participation in complying with the minimum marriage age regulations in order to reduce the incidence of early marriage